2016
DOI: 10.1139/cjas-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of pre-weaning diet with l-arginine has carry-over effect to improve intestinal development in young piglets

Abstract: This study tested the hypothesis that pre-weaning supplemental arginine may have a carry-over effect on intestinal growth and development of piglets immediately after weaning. Fifty-four [Duroc × (Landrace × Yorkshire)] piglets were fed a milk replacer diet supplemented with 0 (control), 4, or 8 g kg −1 of L-arginine from d 4 to 21 of age (6 replicate pens of 3 piglets per group). Piglets were then weaned to a common corn-soybean meal diet and fed for another 21 d. On day 42, 6 pigs per treatment were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…However, it is possible that the ideal dietary ratio of lysine to arginine for young piglets is >100:55 because the study by Kim et al did not involve a higher-arginine-supplemented group. In addition, preweaning supplementation with 0.8% arginine in piglets showed a 10-d carry-over effect of arginine in increasing ADG ( 46 ). Therefore, the requirements of arginine were influenced by birth weight, BW, and age and varied with condition, which necessitates further studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that the ideal dietary ratio of lysine to arginine for young piglets is >100:55 because the study by Kim et al did not involve a higher-arginine-supplemented group. In addition, preweaning supplementation with 0.8% arginine in piglets showed a 10-d carry-over effect of arginine in increasing ADG ( 46 ). Therefore, the requirements of arginine were influenced by birth weight, BW, and age and varied with condition, which necessitates further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, we were also unable to detect significant differences on feed efficiency, daily gain or feed intake in young rabbits fed diets supplemented with 1% Gln (Chamorro et al, 2010). However, studies with Arg seem to be more consistent regarding the positive effects of supplementing this amino acid on preand post-weaning pig performance (Yang et al, 2016). A lack of effect of Arg on performance in our study compared to those in pigs might depend on species differences or dosage used.…”
Section: Discussioncontrasting
confidence: 88%
“…It has been reported that supplementation of L-arginine (0.2 to 1%) enhanced growth performance and alleviated the negative effects of different insults or challenges in young pigs (81,(89)(90)(91). Supplementation of 0.4 to 0.8% L-arginine in pre-weaning diet enhanced intestinal growth and development in early post-weaning period (92). In addition, supplementation of 0.6% L-arginine enhanced small intestinal growth, goblet cell number in intestinal mucosa, intestinal heat shock protein-70 expression in weaned pigs (81).…”
Section: Functional Amino Acidsmentioning
confidence: 99%